Sequencing and annotation of the complete mitochondrial genome of a threatened labeonine fish, - Mohammad Nazrul Islam; Shirin Sultana; Md. Jobaidul Alam (Genomics & Informatics)
The mitochondrial genome of a species is an essential resource for its effective conservation and phylogenetic studies. In this article, we present sequencing and characterization of the complete mitochondrial genome of a threatened labeonine fish, Cirrhinus reba collected from Khulna region of Bangladesh. The complete mitochondrial genome was 16,597 bp in size, which formed a circular double-stranded DNA molecule containing a total of 37 mitochondrial genes (13 protein-coding genes, 2 ribosomal RNA genes, and 22 transfer RNA genes) with two non-coding regions, an origin of light strand replication (OL) and a displacement loop (D-loop), similar structure with other fishes of Teleostei. The phylogenetic tree demonstrated its close relationship with labeonine fishes. The complete mitogenome of Cirrhinus reba (GenBank no. MN862482) showed 99.96% identity to another haplotype of Cirrhinus reba (AP013325), followed by 90.18% identity with Labeo bata (AP011198).